CIN grades possessing different HPV RNA location patterns and RNAscope is helpful tool for distinguishing squamous intraepithelial lesions in difficult cervical cases - Ruichao Chen; Renchao Zhang; Minfen Zhang; Shaoyan Liu; Mingyu Xie; Zhongfeng Yang; Quan Shi; Hui Chen; Hanzhen Xiong; Na Wang; Qingping Jiang (BMC, 2023)
Abstract Background and objectives The precise grading and characterization of cervical intraepithelial neoplasia (CIN) has been the focus of pathologists for a long time. This study aimed to explore known strategies for the grading of CINs. Methods After routine H&E review, 85 lesions graded CIN 1, 2, or 3 were investigated primarily by HPV RNAscope to detect HR-HPV and LR-HPV, in combination with an HPV-DNA test and P16/Ki67 immunohistochemistry (IHC). Then, the 85 cases were divided into a control group (49 cases) and a test group (36 cases). The former consisted of cases with consistency between morphology, HPV DNA detection and P16/Ki67 IHC. We used them to evaluate HPV RNA distribution patterns in CINs of different grades. The latter were ambiguous cases in which pathologists could not confirm the diagnosis because of inconsistencies between morphology, HPV DNA detection and P16/Ki67 IHC. We reassessed them by comparison to the pattern in the control group. Results The expression patterns of HPV mRNA signals were different in different CIN lesions. LSIL/CIN1 lesions were mostly expressed in superficial epithelium with diffuse clustered nuclear or cytoplasmic staining; HSIL/CIN2 were characterised by nuclear/cytoplasmic punctate or diffuse cluster nuclear staining in the mid-surface layer, and scattered nuclear/cytoplasmic punctate staining in basal and parabasal cells; whereas HSIL/CIN3 showed full-thickness nucleus/cytoplasmic scattered staining with a punctate pattern. According to the staining pattern, we corrected the diagnosis of 22 cases (22/36, 61.1%). Conclusion Because of its distinct location pattern, HPV RNAscope has obvious advantages over the HPV-DNA test, and combined with P16/Ki67 IHC, it can help pathologists correctly grade CIN. In addition, it can effectively discriminate true CIN from normal or CIN mimic lesions, such as immature squamous metaplasia, atrophy, and inflammatory/reactive changes. Therefore, HPV RNAscope is a valuable auxiliary diagnostic test to avoid the overtreatment and undertreatment of CIN lesions.